PERAN MEDIA VISUAL GAMBAR DALAM PEMBELAJARAN MENGARTIKULASIKAN SECARA TERTULIS TEKS ARGUMENTASI PADA SISWA KELAS XI SMAN 4 KOTA KEDIRI TAHUN PELAJARAN 2025/2026 - Intan Nuraina Sari; Moch. Muarifin; Andri Pitoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study critically investigates the “role of visual image media in the teaching and learning of argumentative writing skills among eleventh-grade students of SMAN 4 Kediri in the 2025/2026 academic year.” The research is grounded in the observed deficiency in students’ abilities to “generate ideas, construct coherent and logical arguments, and systematically organize argumentative texts.” A quantitative research approach was employed using a quasi-experimental design, specifically a posttest-only control group model. The participants comprised two groups, namely an experimental class consisting of 30 students and a control class consisting of 26 students. Data were collected through writing assessment tests and subsequently analyzed using descriptive statistics and inferential statistics through an Independent Sample T-test. The results demonstrate a significant disparity between the two groups. The experimental class attained a mean score of 92.83, whereas the control class achieved a mean score of 75.00. “The statistical analysis yielded a t-value of 8.113 with a significance level of 0.000 (< 0.05), thereby indicating that the null hypothesis was rejected and the alternative hypothesis was accepted” (Sugiyono, 2022). These findings substantiate that visual image media exerts a significant positive effect on students’ argumentative writing competence. The presence of visual stimuli does not merely function as an auxiliary instructional tool, but rather serves as a “cognitive bridge connecting observation, imagination, and critical reasoning,” thereby enabling students to articulate ideas in a more logical, coherent, and meaningful written form.